PERANCANGAN E-COMMERCE PADA PHOTOBOOTH HANDMADE MANDAHAGE BERBASIS WEB - Sarwinda Purnamasari; Agus Siswanto; M. Riza Pahlevi B (LPPM Universitas Dinamika Bangsa, 2014)
With The birth and rapid development of the cheapest communication infrastructure and the level of its wide acceptance, the use of the internet as a support facility and even as bussiness become increasingly apparentsuperiority. One trend that accompanies the bussiness in the internet network is the E-Commerce . Website development internet world has penetrated in all aspects of life, one of which is a trade area with internet which can make buying and selling and searching for information electronically for example, E-Commerce. In the existing problems Photobooth Handmade Mandahage still not able to penetrate the market share widely, due to the sale of only relying on social media Instagram & Blackberry Massanger so that the sales are not in accordance with the desired target. Therefore, this study provides a solution to the problems that occur with offering applications based E-Commerce website that became a media intermediary to provide information about products Photobooth Handmade Mandahage application is built using the program Dreamweafer CS5, PHP, MySQL database and the authors do development web Engineering methods and using a systems approach Data Flow Diagram, Flowchart, Entity Relationship. Keywords : E-Commerce, Booking, Sales, Internet